Military Spending and Employment in Eastern European Countries: New Evidence from Panel Data Analysis - Abdüsselam Sağın; Barış Kocaarslan (İstanbul Üniversitesi Sosyoloji Dergisi)
This study used the Keynesian theory of employment to discover the relationship between military expenditure and employment in Eastern European countries (Czechia, Estonia, Latvia, Slovenia, Hungary, Slovakia, and Poland) during the postcommunist period. To ensure robust estimates, we considered other economic indicators such as gross domestic product, wages, investments, and government expenditure. To fulfill the main purpose of our research, we used several types of panel autoregressive distributed lag (ARDL) techniques, as well as the panel cointegration and panel Granger-causality tests. The results suggested that there is a cointegrating relationship between employment and other explanatory variables. We found a Granger causality from the explanatory variables of interest (military expenditure, gross domestic product, wage, investment, and government expenditure) to employment. Panel ARDL results suggested that an increase in military expenditure results in an immediate increase in employment, but over a longer period of time the opposite is true. Additionally, over time the gross domestic product and investments had a positive effect on employment, whereas wages and government expenditure harmed employment. Our findings provide useful insights into understanding the employment dynamics of Eastern European countries during the post-Cold War period and present valuable policy implications.